Teknologi Nano Dari Bahan Alam Sebagai Prospek Penerapan Konstruksi Berkelanjutan - Lubis, Nur Azizah; Putri, Mentari Darma (International Journal of Science, Technology and Applications, 2024)
This research explores the benefits of nanotechnology in the construction sector to improve energy efficiency, reduce environmental impact, and create environmentally friendly materials that can be recycled. Using the literature review method, this research analyzes various study results and secondary data related to the application of nanotechnology in construction materials and the utilization of natural materials as additives. The study shows that the application of nanotechnology in concrete can improve its quality, such as accelerating the curing time, reducing cracking and shrinkage, and lowering environmental impact. In addition, natural materials such as nanocellulose, rice husk ash, and coconut fibers have proven to have great potential in strengthening construction materials. Rice husk ash, with its high silica content, is effective as a substitute for conventional silica, enhancing concrete durability and reducing cracking. Meanwhile, coconut fibers provide advantages in tensile strength, flexibility, and earthquake resistance, making them suitable for use in tropical regions. This research underscores the important role of nanotechnology and natural materials in supporting sustainable construction.